PREVALENCE OF LOWER URINARY TRACT SYMPTOMS POST KIDNEY TRANSPLANTATION AND ITS URODYNAMIC PROFILE - Islianti, Putri Iradita; Rahardjo, Harrina Erlianti; Rasyid, Nur; Rodjani, Arry (Indonesian Journal of Urology, 2021)
Objective: This study aimed to describe the urodynamic characteristics of post-transplant kidney patients with LUTS who were indicated for urodynamics. Material & Methods: This research is a cross-sectional study conducted at Cipto Mangunkusumo General Hospital between 2011-2017. Data were collected from patients who had undergone urodynamic examination after kidney transplantation due to LUTS/urinary retention. Data were collected from the patient’s medical record. Results: A total of 536 patients underwent kidney transplants at Cipto Mangunkusumo General Hospital from 2011-2017. Eleven patients (2%) developed LUTS and then underwent urodynamic examination with an average age of 41.4 (30.1 ± 52.6) years. Six patients (55%) had type 2 diabetes mellitus (DM) and 5 patients (45%) had hypertension (HT). A total of 6 out of 11 patients (54%) experienced urinary retention of which 4 subjects (67%) had decreased bladder compliance, 4 (67%) patients experienced detrusor overactivity (DO), 3 patients (50%) had bladder outlet obstruction (BOO), while 2 patients (33%) experienced detrusor underactivity (DU) respectively. Of 5 patients without urinary retention, decreased bladder compliance was found in 1 patient (20%), DO in 2 patients (40%), BOO in 1 patient (20%), and no subject experienced DU. In both groups, no subject was discovered to experience any urinary incontinence. Conclusion: Small number of post renal transplantation patients developed LUTS and half of which accompanied by urinary retention. Among these patients, urodynamic examination revealed detrusor overactivity as the most common underlying problem followed by decreased bladder compliance, BOO, and detrusor underactivity